Photophysicochemical properties of [Tetrakis 6-(tert-butyl)-2,3-dihydrobenzo [b] [1,4] dioxine) phthalocyaninato] In(III) and Zn(II) with very high singlet oxygen quantum yield - Zeki, K.; Lokmaci, E.; Dogu, Ezgi; Khene, S.; Salih, B.; Canlica, M. (ELSEVIER SCIENCE SA, 2021)
Synthesis and photophysicochemical properties of [tetrakis 6-(tert-butyl)-2,3-dihydrobenzo [b] [1,4] dioxine) phthalocyaninato] In(III) (InPc-4) and [tetrakis 6-(tert-butyl)-2,3-dihydrobenzo [b] [1,4] dioxine) phthalocyaninato] Zn(II) (ZnPc-5) containing 4-tert-butylcatechol at the peripheral positions are synthesised for application as photosensitisers in photodynamic therapy (PDT). Fluorescence quantum yield, singlet oxygen quantum yield and photodegradation quantum yield were determined for each complex. High singlet oxygen quantum yield of 0.84 and 0.86 (in THF) were obtained for InPc-4 and ZnPc-5, respectively. Density functional theory (DFT) and time dependent density functional theory (TDDFT) were carried out to rationalise the experimental results.
Keywords: Singlet oxygen quanum yield; 4-tert-butylcatechol; Zinc phthalocyanine; Indium phthalocyanine; Density funcitonal theory; Photodynamic therapy; ISOMERS; PHOTOSENSITIZERS; PORPHYRIN; Chemistry